CHATGPT’S IMPACT ON THE UNIQUENESS OF LAUTECH UNDERGRADUATE FINAL-YEAR STUDENTS’ PROJECTS - Owolabi, Abiola Timothy; Adewole, Oluwabukunmi Isaiah; Adewole, Oluwabukunmi Isaiah; Akinsola, Victor Olajide; Oladapo, Olasunkanmi James; Idowu, Janet Iyabo (FUDMA JOURNAL OF SCIENCES, 2025)
The emergence of artificial intelligence (AI) tools like OpenAI’s ChatGPT has brought about challenges for academic researchers and higher education institutions, especially when drafting final-year projects for students. Assessing traditional human contributions and differentiating between human and AI authorship have surfaced as significant academic issues. This study investigates the prevalence and potential effects of ChatGPT on the originality and creativity of final-year student projects in a higher education institution in south-west Nigeria. A total of one hundred and fifty-two students (152) participated in the survey, and descriptive analysis, along with an independent chi-squared test, was employed for the study. Approximately half of the students in the survey involved ChatGPT to varying degrees in writing different aspects of their project. Among the different parts of the project, data analysis garnered the least attention, while the Abstract attracted the most attention. ChatGPT awareness was not affected by the age group but was influenced by gender. According to the study’s results, there were significant gender-based disparities in students’ awareness of ChatGPT (p-value < 0.05), with 44.1% indicating a moderate level of familiarity and 58.6% utilizing it for educational purposes. Higher education institutions should not only caution students about the perils of excessively relying on tools like ChatGPT for academic writing but also cultivate a research culture that highly values originality and innovation.